CO2 Adsorption from Biogas Using Amine-Functionalized MgO - Preecha Kasikamphaiboon; Uraiwan Khunjan (International Journal of Chemical Engineering)
Biogas is a renewable fuel source of methane (CH4), and its utilization as a natural gas substitute or transport fuel has received much interest. However, apart from CH4, biogas also contains carbon dioxide (CO2) which is noncombustible, thus reducing the biogas heating value. Therefore, upgrading biogas by removing CO2 is needed for most biogas applications. In this study, an amine-functionalized adsorbent for CO2 capture from biogas was developed. Mesoporous MgO was synthesized and functionalized with different tetraethylenepentamine (TEPA) loadings by wet impregnation technique. The prepared adsorbents (MgO-TEPA) were characterized by X-ray diffraction (XRD) and N2 adsorption-desorption. The CO2 adsorption performance of the prepared MgO-TEPA was tested using simulated biogas as feed gas stream. The results show that the CO2 adsorption capacities of the adsorbents increase with increasing TEPA loading. The optimum TEPA loading is 40 wt.%, which gives the highest CO2 adsorption capacity of 4.98 mmol/g. A further increase in TEPA loading to 50 wt.% significantly reduces the CO2 adsorption capacity. Furthermore, the stability and regenerability of the adsorbent with 40% TEPA loading (MgO-TEPA-40) were studied by performing ten adsorption-desorption cycles under simulated biogas and real biogas conditions. After ten adsorption-desorption cycles, MgO-TEPA-40 shows slight decreases of only 5.42 and 5.75% of CO2 adsorption capacity for the simulated biogas and biogas, respectively. The results demonstrate that MgO-TEPA-40 possesses good stability and regenerability which are important for the potential application of this amine-based adsorbent.